DEcompressive Surgery plus hypoTHermia for Space-Occupying Stroke (DEPTH-SOS): A Protocol of a Multicenter Randomized Controlled Clinical Trial and a Literature Review. Issue 5 (July 2013) - Neugebauer, Hermann; Kollmar, Rainer; Niesen, Wolf-Dirk; Bösel, Julian; Schneider, Hauke; Hobohm, Carsten; Zweckberger, Klaus; Heuschmann, Peter U.; Schellinger, Peter D.; Jüttler, Eric; ,
Rationale: Although decompressive hemicraniectomy clearly reduces mortality in severe space-occupying middle cerebral artery infarction (so-called malignant middle cerebral artery infarction), every fifth patient still dies in the acute phase and every third patient is left with moderate to severe disability. Therapeutic hypothermia is a neuroprotective and antiedematous treatment option that has shown promising effects in severe stroke. A combination of both treatment strategies may have the potential to further reduce mortality and morbidity in malignant middle cerebral artery infarction, but needs evaluation of its efficacy within the setting of a randomized clinical trial. Aims: The DEcompressive surgery Plus hypoTHermia for Space-Occupying Stroke (DEPTH-SOS) trial aims to investigate safety and feasibility of moderate therapeutic hypothermia (33°C ± 1) over at least 72 h in addition to early decompressive hemicraniectomy (≤48 hours after symptom onset) in patients with malignant middle cerebral artery infarction. Design: The DEcompressive surgery Plus hypoTHermia for Space-Occupying Stroke is a prospective, multicenter, open, two-arm (1:1) comparative, randomized, controlled trial. Study outcomes: The primary end-point is mortality at day 14. The secondary end-points include functional outcome at day 14 and at 12 months follow-up, and complications related to hypothermia. Discussion: The results of this trial will provide data on safety and feasibility of moderate hypothermia in addition to decompressive hemicraniectomy in malignant middle cerebral artery infarction. Furthermore, efficacy data on early mortality and long-term functional outcome will be obtained, forming the basis of subsequent trials.